Kajian Status Mutu Air Sungai Akibat Buangan Air Lindi TPA Piyungan di Kabupaten Bantul - Syafrudin Syafrudin; Indah Susilowati; Farida Afriani Astuti (School of Postgraduate Studies, Diponegoro Univer, 2023)
This research was conducted along a tributary that empties into the Opak River in Piyungan District. This study aimed to examine the characteristics of leachate from the Piyungan landfill, river water quality, and the status of river water quality due to the discharge of leachate from the Piyungan landfill. The research method used is a survey method with sampling and field observations. Purposive sampling is used to take river sample points. There are five sample points taken with 15 test parameters used to analyze river water quality, including COD, BOD, TSS, TDS, Zinc (Zn), Iron (Fe), Chromium, Copper (Cu), Lead (Pb), Mercury (Hg), pH, temperature, turbidity, color, and total coliform. River water quality status is obtained by calculating the Pollution Index (IP) of class II quality standard, Governor of DIY Regulation Number 20 of 2008, without the total coliform parameter. Based on the analysis results, the characteristics of the leachate water of the Piyungan TPA have concentrations of BOD, COD, TSS, TDS, and Iron (Fe), which exceed the quality standards of Yogyakarta Special Region Regulation Number 7 of 2016. River water quality shows that parameters BOD, COD, TSS, TDS, Zinc (Zn), Iron (Fe), turbidity, color, and total coliform exceed class II water quality standards regulation of the Governor of the Special Region of Yogyakarta Number 20 of 2008. The highest pollution load in rivers is Total Coliform, BOD, and COD. The status of river water quality from all sample point locations has the status of heavily polluted water (Point S1), moderately polluted (Point S2, S3, S4), and lightly polluted (Point S5). Thus, river water quality around the Piyungan landfill has decreased due to the discharge of leachate from the Piyungan landfill and community activities around the river.